An Al-doped ZnO electrode grown by highly efficient cylindrical rotating magnetron sputtering for low cost organic photovoltaics - Park, Jun-Hyuk; Ahn, Kyung-Jun; Park, Kang-Il; Na, Seok-In; Kim, Han-Ki (IOP PUBLISHING LTD, 2010)
We report the characteristics of Al-doped zinc oxide (AZO) films prepared by a highly efficient cylindrical rotating magnetron sputtering (CRMS) system for use as a transparent conducting electrode in cost-efficient bulk hetero-junction organic solar cells (OSCs). Using a rotating cylindrical type cathode with an AZO target, whose usage was above 80%, we were able to obtain a low cost and indium free AZO electrode with a low sheet resistance of similar to 4.59 Omega/sq, a high transparency of 85% in the visible wavelength region and a work function of 4.9 eV at a substrate temperature of 230 degrees C. Moreover, the neutral poly(3,4-ethylenedioxythiophene) : poly(styrenesulfonate) based OSC fabricated on the CRMS-grown AZO electrode at 230 degrees C showed an open circuit voltage of 0.5V, a short circuit current of 8.94 mAcm(-2), a fill factor of 45% and power conversion efficiency of 2.01%, indicating that CRMS is a promising cost-efficient AZO deposition technique for low cost OSCs.